Business networks, production chains, and productivity: A theory of input-output architecture - Ezra Oberfield (Federal Reserve Bank of Chicago, 2011)
This paper studies an analytically tractable model of the formation and evolution of chains of production. Over time, entrepreneurs accumulate techniques to produce their good using goods produced by other entrepreneurs and labor as inputs. The value of a technique depends on both the productivity embodied in the technique and the cost of the particular input; when producing, each entrepreneur selects the technique that delivers the best combination. The collection of known production techniques form a dynamic network of potential chains of production: the input-output architecture of the economy. Aggregate productivity depends on whether the lower cost firms are the important suppliers of inputs. When the share of intermediate goods in production is high, the lower cost firms are selected as suppliers more frequently. This raises aggregate productivity and also increases the concentration of sales of intermediate goods.
Keywords: O31; O33; O47; 330; Networks; Productivity; Supply Chains; Ideas; Diffusion